THE STRUCTURAL CHARACTER OF LABOR PRECARITY IN PERU - LUST, Jan (2021)
The The role of Peru in the international division of labor is the structural condition for labor precariousness in the country. At a more concrete level, labor precariousness is the expression of the economic and business structure of the country. An economic structure heavily dependent on the non-tradable sectors and a business structure dominated by micro business undertakings do not permit the eradication of precarious labor conditions as economic growth hinges on economic progress abroad and precariousness is the source of profit of micro companies. Labor precariousness in Peru is not an automatic result of the country’s role in the globalized capitalist world, but the social and economic consequence of the neoliberal policies implemented in the 1990s and, in particular, of the current development model in place.